Shift in Payment Method Preferences from Cash to Sharia-Based Mobile Banking: A Study of Muslim Consumer Behavior on Bawean Island - Muhammad Rahel; Andrian Firman Shah; Raudatul Jannah; Rifky Ananda Rahman; Qomarul Haq; Alif Sandika Putra; Mudarrisa; Salsabilaturribi; Murtasiyah; Inayatul Fatimah (CV. Civiliza Publishing, 2025)
This study aims to analyze the determinants of the shift in payment preferences from cash to Sharia-based mobile banking among Muslim consumers on Bawean Island. This study highlights the adaptation of financial technology in an archipelagic region with strong religious cultural characteristics and dependence on the migrant economy. The research method used a descriptive quantitative approach through a survey of 107 respondents residing in Sangkapura and Tambak subdistricts, with demographic variations ranging from students to entrepreneurs. The results reveal that technology adoption is dominated by younger age groups (Generation Z and Millennials). Utility factors such as transaction speed, bill payment efficiency, and ease of receiving remittances from migrant relatives are the main functional drivers. Substantially, religious aspects including halal guarantees, riba-free principles, and the integration of worship features proved to be distinguishing factors that built user trust and peace of mind. Although perceptions of application security were relatively high, infrastructure constraints in the form of unstable internet signals remained a significant technical obstacle in the region. Overall, it is concluded that sharia mobile banking in Bawean has transformed into a vital solution that bridges the needs of modern economic transactions with compliance with Islamic values.